Case reportMycosis fungoides - a case report - Michalecki, Łukasz; Głowacki, Grzegorz; Urbańczyk, Hubert; Gabryś, Dorota (Menopause Review/Przegląd Menopauzalny, 2015)
Mycosis fungoides (MF) is a form of T-cell lymphoma that initially manifests itself in the skin and may mimic other skin conditions related to skin aging in postmenopausal women. In some patients, extra-cutaneous dissemination may occur, usually to the lymph nodes, spleen, bone marrow, and other organs. It develops gradually from patches to more infiltrated plaques and eventually to tumors. Although our understanding of the etiopathogenesis of this disease is still incomplete, due to the recent introduction of some sophisticated therapeutic methods, we are able to achieve remission of variable duration with minimization or even elimination of symptoms. This report documents a case of an 82-year-old female patient, with histologically proven mycosis fungoides, who was treated at the Department of Radiation Oncology, Cancer Centre in Gliwice, Poland, with two courses of total skin electron therapy. The report presents some difficulties with early diagnosis and treatment, as well as the effectiveness of the clinicians’ perseverance in the management of such an unpredictable disease.